Governance of Technical Education in India : Key Issues, Principles, and Case Studies - Blom, Andreas; Cheong, Jannette (World Bank, 2012)
Tertiary education, and in particular technical and engineering education, is critical to India's aspirations of strengthening its reputation as a major competitive player in the Global knowledge economy. The system is huge and complex, and there is a consensus that reforms are imperative. Issues of fair access and affordable participation in higher education are critical if India is to empower its people with educational opportunities that allow individual potential to be fulfilled, and allow more Indian graduates opportunities for employment and to compete in an international arena. There are approximately 2,400 technical and engineering institutions across India's 30 states, of which less than 8 percent of public institutions are autonomous. The demand for tertiary education continues. There has been a phenomenal growth in the number of private colleges across India in the last 20 years. Private colleges now deliver 85 percent of all technical and engineering education. The significant changes in supply and demand make it increasingly important to ensure that tertiary education systems and institutions are effectively and efficiently governed and managed to meet the needs of industry and society. As key national changes are imminent, stakeholder groups represented at the Learning Forum emphasized the importance of working in partnership, so that overlapping interests can support a more effective delivery of education to meet the needs of society and industry. Good governance is an area where effective partnerships are crucial. Strengthening links with industry and local communities could also support a range of development opportunities for courses, faculty and most importantly the student experience and education and research outcomes. These priorities are in line with the Second Phase of the Technical Education Quality Improvement Project and the need for ongoing capacity building. Developing effective governance will underpin long term developments.